2003
DOI: 10.1093/jac/dkg337
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic profile of daptomycin against Enterococcus species and methicillin-resistant Staphylococcus aureus in a murine thigh infection model

Abstract: These data reveal the potent in vivo bactericidal activity of daptomycin against MRSA and Enterococcus species using clinically achievable drug exposures (dose 4-6 mg/kg per day) currently under investigation in man.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
68
0
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 13 publications
3
68
0
3
Order By: Relevance
“…They concluded that more studies with strains that grew better were needed because low growth (⌬G 26Ϫ2 Ͻ 0.4 log 10 CFU/g) led to overestimation of the drug's efficacy against E. faecium (AUC/MIC for stasis was 0.94 to 1.67) compared to that with S. aureus (388 to 537) or S. pneumoniae (75 to 237) (13). Other authors have obtained similarly biased results (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that more studies with strains that grew better were needed because low growth (⌬G 26Ϫ2 Ͻ 0.4 log 10 CFU/g) led to overestimation of the drug's efficacy against E. faecium (AUC/MIC for stasis was 0.94 to 1.67) compared to that with S. aureus (388 to 537) or S. pneumoniae (75 to 237) (13). Other authors have obtained similarly biased results (9).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the usual lack of a full doseresponse curve hinders the determination of pharmacokinetic/ pharmacodynamic (PK/PD) indices necessary to translate the results to humans (5,7). Moreover, the bacterial growth in all enterococcal models is either not quantified (e.g., peritonitis model) (8), poor (ϳ1 log 10 CFU/g), or even negative (e.g., thigh infection) (9,10), and the variability is high (e.g., rabbit endocarditis models) (11), particularly with vancomycin (VAN)-resistant enterococcus (VRE) strains (12). Negligible growth and high-level dispersion may lead to inaccurate estimations of antibiotic PD, as has been the case with daptomycin (13).…”
mentioning
confidence: 99%
“…Animal model data suggest that the AUC/minimum inhibitory concentration (MIC) ratio is the pharmacodynamic parameter that best describes daptomycin's activity (15)(16)(17)(18). However, the AUC/ MIC ratio associated with maximal effect varies.…”
Section: Monte Carlo Simulation (Mcs)mentioning
confidence: 99%
“…Animal model data suggest that daptomycin is a concentration-dependent antibiotic, and the AUC/ MIC ratio is the pharmacodynamic (PD) parameter that best describes its activity (3,5,9,11). However, the AUC/MIC ratio associated with maximal effect has varied (3,5,9,11). Given the lack of a definitive AUC/MIC threshold, especially for patients with bloodstream infections, the distribution of AUC values (the PD target most closely linked to effect) for any candidate HD dosing scheme should at least be comparable to what is typically observed in non-HD patients.…”
mentioning
confidence: 99%
“…For efficacy, the primary exposure target was the area under the curve (AUC). Animal model data suggest that daptomycin is a concentration-dependent antibiotic, and the AUC/ MIC ratio is the pharmacodynamic (PD) parameter that best describes its activity (3,5,9,11). However, the AUC/MIC ratio associated with maximal effect has varied (3,5,9,11).…”
mentioning
confidence: 99%